A study to know awareness of investors in SME sector - Dr. Shambhaji Shivaji Jadhav (Innovative Research Thoughts, 2022)
Since businesses, especially SMEs, are vital to the health of the economy, it is necessary to investigate the problems that arise from the investment procedures they undertake. Economic e ects as a consequence of the executed investment are critical from the perspective of the firm. The study's objective was to compare the outcomes of capital expenditures made by companies in Poland's Maopolska region that received European Union (EU) subsidies with those made by companies that used other funding mechanisms (i.e., no EU help was used). This study is the first of its kind to analyze and report information on corporate investments, particularly as it relates to businesses receiving EU funding. For this issue, there is no scientific literature that provides a comparative analysis of business investments (concerning EU subsidies). To address this knowledge gap, this study compares the effects of investment activities among companies that get and do not receive EU subsidies. The research relied on a thorough review of relevant domestic and international literature, as well as quantitative and qualitative analyses of the findings of a survey administered to 160 businesses using the CSAQ technique and supplemented by interviews with chosen respondents. Information is presented with both a descriptive and statistical focus. In addition, we employed a multiple linear regression model (MLR) to test our assumptions. According to studies, businesses may benefit from investing activities regardless of where the money for such operations comes from. The success of a business may be accomplished regardless of who provides the capital. Despite this, company representatives whose have obtained EU subsidies tend to be more optimistic about their positions in the market after investment. In general, businesses that have received EU subsidies see investment more favorably as a determinant in the company's future success. Furthermore, characteristics that affect the evaluation of businesses' financial standing were discovered using the MLR model. This article fills in some of the blanks in our understanding of the economic e ects of investments made by Polish SMEs that did and did not get European Union subsidies between 2007 and 2015.